Unveiling the Performance of Co-Assembled Hybrid Nanocarriers: Moving towards the Formation of a Multifunctional Lipid/Random Copolymer Nanoplatform - Efstathia Triantafyllopoulou; Diego Romano Perinelli; Aleksander Forys; Pavlos Pantelis; Vassilis G. Gorgoulis; Nefeli Lagopati; Barbara Trzebicka; Giulia Bonacucina; Georgia Valsami; Natassa Pippa; Stergios Pispas (MDPI AG, 2024)
Despite the appealing properties of random copolymers, the use of these biomaterials in association with phospholipids is still limited, as several aspects of their performance have not been investigated. The aim of this work is the formulation of lipid/random copolymer platforms and the comprehensive study of their features by multiple advanced characterization techniques. Both biomaterials are amphiphilic, including two phospholipids (1,2-dioctadecanoyl-sn-glycero-3-phosphocholine (DSPC), 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC)) and a statistical copolymer of oligo (ethylene glycol) methyl ether methacrylate (OEGMA) and 2-(diisopropylamino) ethyl methacrylate (DIPAEMA). We examined the design parameters, including the lipid composition, the % comonomer ratio, and the lipid-to-polymer ratio that could be critical for their behavior. The structures were also probed in different conditions. To the best of the authors' knowledge, this is the first time that P(OEGMA-co-DIPAEMA)/lipid hybrid colloidal dispersions have been investigated from a membrane mechanics, biophysical, and morphological perspective. Among other parameters, the copolymer architecture and the hydrophilic to hydrophobic balance are deemed fundamental parameters for the biomaterial co-assembly, having an impact on the membrane's fluidity, morphology, and thermodynamics. Exploiting their unique characteristics, the most promising candidates were utilized for methotrexate (MTX) loading to explore their encapsulation capability and potential antitumor efficacy in vitro in various cell lines.